(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this paper we introduce and study another types of functions in a topological spaces namely , -compact and -coercive by using the concept of -open sets . Also we investigate some properties of these concepts and the relation between them.